2009
DOI: 10.1159/000235741
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Infection of Cultured Mouse Macrophages

Abstract: The interactions of tick-borne encephalitis virus (TBEV) with mouse macrophages were studied at the electron microscopic level. The cultured mouse macrophages were sensitive to infection with TBEV strain Hypr (a highly neuroinvasive and neurovirulent strain for laboratory mice) and produced relatively high virus titers. However, these macrophage cells remained morphologically inactivated. Viral particles were located mainly in the ER but were also present in other exocytic compartments. No virus production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…We have demonstrated that TBEV is able to adhere from the virus containing liquid to the surface of the neutrophils and resident macrophages, penetrate into the cells, and reproduce in these cells. Similar data on selective adsorption to monocytes/macrophages were obtained while studying the interaction of these cells with TBEV (Ahantarig et al, 2009). Morphological examination of the cell culture infected by virulent strains TBEV revealed the features of the cytopathic action of this virus on the macrophages in contrast with the cells infected by avirulent strains.…”
Section: Resultssupporting
confidence: 66%
“…We have demonstrated that TBEV is able to adhere from the virus containing liquid to the surface of the neutrophils and resident macrophages, penetrate into the cells, and reproduce in these cells. Similar data on selective adsorption to monocytes/macrophages were obtained while studying the interaction of these cells with TBEV (Ahantarig et al, 2009). Morphological examination of the cell culture infected by virulent strains TBEV revealed the features of the cytopathic action of this virus on the macrophages in contrast with the cells infected by avirulent strains.…”
Section: Resultssupporting
confidence: 66%
“…Intradermal injection followed by ex vivo analysis revealed a primary infection of local dendritic cells, neutrophils, and monocytes (36). Furthermore, cell culture experiments showed that macrophages are infectible and produce large amounts of viral titers (37). Our results in vivo show that LGTV is indiscriminate and that it can target different hematopoietic and nonhematopoietic cell types in the peripheral and CNS tissues.…”
Section: Discussionmentioning
confidence: 67%
“…However, POWV directly infects macrophages (Fig. 2 ) at an early stage in the tick-feeding site [ 53 , 54 ], which potentially triggers the activation of NK and NKT cells to produce IFNγ causing a cytotoxic response in POWV virions (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%